2002
DOI: 10.1001/archinte.162.20.2285
|View full text |Cite
|
Sign up to set email alerts
|

Postponed Development of Disability in Elderly Runners

Abstract: Running and other aerobic exercise in elderly persons protect against disability and early mortality, and are associated with prolongation of a disability-free life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
48
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 41 publications
5
48
0
2
Order By: Relevance
“…These findings were investigated longitudinally (over 13 years) by Wang et al 6 The study sample consisted of 961 individuals classified as runners and nonrunners (who had never run), with an initial age of 50-72 years. Aiming to determine the degree to which disability could be delayed, the study compared the development of such disabilities between the groups, finding that the runners group delayed this process by approximately 8.7 years (CI 95% 5.5 to 13.7) compared to the nonrunners group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These findings were investigated longitudinally (over 13 years) by Wang et al 6 The study sample consisted of 961 individuals classified as runners and nonrunners (who had never run), with an initial age of 50-72 years. Aiming to determine the degree to which disability could be delayed, the study compared the development of such disabilities between the groups, finding that the runners group delayed this process by approximately 8.7 years (CI 95% 5.5 to 13.7) compared to the nonrunners group.…”
Section: Discussionmentioning
confidence: 99%
“…The results indicate that regular physical exercise, or in this case, predominantly aerobic exercise, can delay the onset of disability, morbidity and mortality, influencing the quality of life of individuals, as disability is linked to the condition of independently performing activities of daily living. 6,15,25 Chronic diseases are indirectly related to CRF. The CRF of elderly women suffering from two and three chronic diseases was 15% and 23% (as measured by maximal oxygen uptake in a maximum treadmill test using a metabolic analyzer, measuring gas exchange with each breath) lower, respectively, than those who did not have any chronic disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent longitudinal study reported on individuals up to the age of 72. 68 However, there are other reports that include elderly runners beyond age 72 in various physiological 14,70 and biomechanical studies. 38 There is also little in the current literature that examines the reliability and validity of many of the commonly used clinical tests and measures for the hip.…”
Section: Physical Therapy Considerationsmentioning
confidence: 99%